Mesoporous Silica from Rice Husk Ash - V. R. Shelke; S. S. Bhagade; S. A. Mandavgane (Bulletin of Chemical Reaction Engineering & Catalysis, 2010)
Mesoporous silica is used as a raw material in several areas: in preparation of catalysts, in inks, as a concrete hardening accelerator, as a component of detergents and soaps, as a refractory constituent etc. Sodium silicate is produced by reacting rice hull ash (RHA) with aqueous NaOH and silica is precipitated from the sodium silicate by acidification. In the present work, conversion of about 90% of silica contained in RHA into sodium silicate was achieved in an open system at temperatures of about 100 °C. The results showed that silica obtained from RHA is mesoporous, has a large surface area and small particle size. Rice Husk is usually mixed with coal and this mixture is used for firing boilers. The RHA therefore, usually contains carbon particles. Activated carbon embedded on silica has been prepared using the carbon already present in RHA. This carbon shows good adsorption capacity. © 2010 by Authors, Published by BCREC Group. This is an open access article under the CC BY-SA License (https://creativecommons.org/licenses/by-sa/4.0)